Phase Behavior of Lipid Bilayers: A Dissipative Particle Dynamics Simulation Study. Issue 5 (17th April 2018) - Lu, Teng; Guo, Hongxia
Abstract: Mesoscale simulations are performed to investigate the phase behavior of double‐tail lipid bilayers as a function of temperature and head‐group interaction. Depending on the lipid structure, the simulations reproduce the experimental phase diagrams including the interdigitated structure found in the experimental research. The area per surfactant, the bilayer thickness, the orientational order parameters and the chain overlap parameter are computed and the results show how they depend on the surfactant structure and temperature. The interdigitated structure is induced by increasing the strength of the repulsive interaction between the head‐groups. Therefore, the ability of the model to clarify some of the experimental questions related to the structure of the bilayer, including the interdigitated structure, and to guide the experimental research is confirmed. Abstract : With the size of the head‐groups enlarging, the increasing of the head/tail size mismatch causes the rearrangement of the tail (from perpendicular to tilted and at last interdigitated); through a heating process, the bilayer will melt the order phase domain into disorder or enlarge the disorder domain resulting in the reduction of the system order.